Challenges faced by doctors and nurses in the emergency department: An integrated review - Gopal Singh Charan; Raman Kalia; Sunil Kumar Dular; Rajesh Kumar; Kiranpreet Kaur (Journal of Education and Health Promotion)
Healthcare professionals in emergency departments (EDs) navigate multifaceted challenges, including strenuous environments and complex situations inherent to this high-pressure setting. This research examines the dynamics of emergency medicine, highlighting issues such as ED overcrowding, resource constraints, the emotional and ethical dilemmas of end-of-life care, and the implications of integrating advanced technologies like Radio Frequency Identification (RFID). The study paves the way for potential policy reforms, educational advancements, and administrative strategies to enhance healthcare delivery in emergencies by analyzing these challenges in detail. We used thorough review methodology to analyze global evidence from 2002 to 2023, systematically searching databases like MEDLINE, Web of Science, ProQuest, and Google Scholar with a blend of search terms, Medical Subject Headings (MeSH), refining the search strategy with Boolean operators “AND” and “OR” to improve search results. A PRISMA flow diagram aided the careful selection of studies, while Zotero-6 helped remove duplicates. This collaborative process pinpointed key areas of interest, such as workload, burnout, ethics, and technology in emergency care, ensuring comprehensive review. We focused on including peer-reviewed English articles from the last twenty years, covering review articles, original research, systematic reviews, and meta-analyses. We excluded unpublished theses and nonrelevant studies. This approach provided detailed overview of the challenges and complexities characterizing the emergency care landscape, suggesting ways to enhance practice and policy.